Aligning Gross National Happiness, Sustainable Development Goals, and Traditional Ecological Knowledge: A Path to Holistic Well-being - Nepal, Tej Kumar (Indonesian Journal of Social and Environmental Issues (IJSEI), 2024)
To promote sustainable development and holistic well-being, this article examines the connections between Traditional Ecological Knowledge (TEK), the Sustainable Development Goals (SDGs), and Gross National Happiness (GNH). GNH emphasizes environmental conservation, cultural preservation, and socioeconomic advancement, but the SDGs provide a complete framework for tackling global issues. With its roots in local and indigenous populations, TEK offers essential perspectives on environmental management and cultural preservation. By giving marginalized populations more authority, TEK integration into development plans improves biodiversity protection, guarantees the preservation of indigenous knowledge, and advances social justice. By acknowledging the interdependence of the material, spiritual, and environmental aspects of well-being, we may build resilient, inclusive, and sustainable futures.